Galactic wind X-ray heating of the intergalactic medium during the Epoch of Reionization - Meiksin, Avery; Paardekooper, Jan-Pieter (Monthly notices of the Royal Astronomical Society, 2017)
Abstract. The diffuse soft X-ray emissivity from galactic winds is computed during the Epoch of Reionization (EoR). We consider two analytic models, a pressure